The Impact of Electronic Publishing on Scholarly Communication: A Forum on the Future, October 26-27, 2000, University of Illinois at Urbana-Champaign Libraries - Jane Duffy (Issues in Science and Technology Librarianship, 2000)
The article summarizes the "A Forum on the Future" event held in October 2000 at the University of Illinois at Urbana-Champaign Libraries. This event addressed the academic community's growing concerns about the increasing numbers, titles and prices of scholarly scientific publications, especially as they now exceed the capacity of many libraries' current resources to make these materials accessible.